Enhancing Ion Transfer in Overlimiting Electrodialysis of Dilute Solutions by Modifying the Surface of Heterogeneous Ion-Exchange Membranes - Natalia Pismenskaya; Nadezhda Melnik; Ekaterina Nevakshenova; Kseniya Nebavskaya; Victor Nikonenko (International Journal of Chemical Engineering)
The desalination of dilute NaCl solutions with heterogeneous Russian commercial and modified ion-exchange membranes was studied in a laboratory cell imitating desalination channels of large-scale electrodialysers. The modification was made by casting a thin film of a Nafion-type material on the surface of cation-exchange membrane, and by processing with a strong polyelectrolyte the surface of anion-exchange membrane. It was shown that the modifications resulted in an increase of mass transfer coefficient and in a decrease in water splitting rate, both by up to 2 times. The effect of mass transfer growth is explained by higher surface hydrophobicity of the modified membrane that enhances electroconvection. The decrease in water splitting rate in the case of cation-exchange membrane is due to homogenization of its surface layer. In the case of anion-exchange membrane the effect is due to grafting of quaternary ammonium bases onto the original membrane surface layer. The suppression of water splitting favors development of electroconvection. In turn, intensive electroconvection contributes to deliver salt ions to membrane surface and thus reduces water splitting.